UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI DAN PEMAHAMAN MATEMATIK SISWA - Imelda . (Study Program of Mathematics Education of Unimed Postgraduate Program, 2009)
The aims of this study are conducted to know: (1) the comprehension and improvement of students ability of mathematical communications after studying cooperative learning model think-pair-share type with media software Autograph, (2) the students design in answering math comprehension and communications, (3) students responds to cooperative learning model think-pair-share type with media software Autograph. This research is a classroom action research. The subject of this research is 40 students of grade XI SMK N 9 Medan. The research object is the improvement of students ability in mathematical comprehension and communication through cooperative learning model think-pair-share type with media software Autograph at discussion of transformation. The instruments are pretest, communication mathematical test, comprehension mathematical test, student note, observation sheets, and students respond. The reliable of pretest, comprehension mathematical test cycle 1 and 2 is 0,86 and the reliable of communication mathematical test is 0,88. This study consisted of 2 cycles of the first cycle consisted of 4 meetings and the second cycle consisted of 2 meetings. The result of study show that the (1) application of cooperative learning model think-pair-share type with media software Autograph can improve the ability of mathematical comprehension and mathematical communications of student, (2) the design in answering math communications and math comprehension are graphic is true and complete, the description of graphic is not complete enough, the description of graphic is true and complete, the description of graphic is not complete. (3) Students respond of cooperative learning model think-pair-share type with media software Autograph is good. Based on this conclusion it is expected that the teachers can apply cooperative learning model think-pair-share type with media software Autograph to improve the ability of mathematical comprehension and mathematical communications of student.